Effects of an increase in intensity during tapering on 1500-m running performance - Spilsbury, K. L.; Nimmo, M. A.; Fudge, B. W.; Pringle, J. S. M.; Orme, M. W.; Faulkner, S. H. (Applied Physiology, Nutrition, and Metabolism, 2019)
We examined the effect of completing the final interval training session during a taper at either (i) race pace (RP) or (ii) faster than RP on 1500-m running performance and neuromuscular performance. Ten trained runners (age, 21.7 ± 3.0 years; height, 182.9 ± 7.0 cm; body mass, 73.4 ± 6.8 kg; and personal best 1500-m time, 4:17.5 ± 0:26.9 min) completed 2 conditions consisting of 7 days of regular training and a 7-day taper, separated by 3 weeks of training. In 1 condition, the taper was prescribed using prediction models based on the practices of elite British middle-distance runners, with the intensity of the final interval session being equal to 1500-m RP. The taper was repeated in the high-intensity (HI) condition, with the exception that the final interval session was completed at 115% of 1500-m RP. A 1500-m treadmill time trial and measures of maximal voluntary contraction (MVC) and rate of force development (RFD) were completed before and after regular training and tapering. Performance was most likely improved after RP (mean ± 90% confidence limits, 10.1 ± 1.6 s), and possibly beneficial after HI (4.2 ± 12.0 s). Both MVC force (p = 0.002) and RFD (p = 0.02) were improved after tapering, without differences between conditions. An RP taper based on the practices of elite middle-distance runners is recommended to improve performance in young, subelite runners. The effect of this strategy with an increase in interval intensity is highly variable and should be implemented with caution.